Association between 25(OH)D3 Levels and the Presence of COVID-19 Symptoms - Dessy Hermawan; Nurul Aryastuti; Nova Muhani; Syafik Arisandi; Made Prativi (Cell and BioPharmaceutical Institute, 2023)
Background: Recently, there have been studies reporting a relationship between vitamin D levels in the blood and the immune system. This study aimed to analyze the association between vitamin D levels and symptoms of coronavirus disease 2019 (COVID-19).Materials and methods: This study was an analytical survey study with a cross-sectional approach, with lecturers at Universitas Malahayati that have been infected with COVID-19 in 2022 as subjects. Total 47 subjects were included. Subjects were fasted overnight, then blood samples were taken from subjects in the next morning. The blood was centrifuged, then the serum was separated for examination by the direct competitive chemiluminescence immunoassay (CLIA) method using Architect 25-OH Vitamin D Reagent. Data was analyzed using logistic regression.Results: None of the subjects had normal blood levels of 25(OH)D3 and almost half (48.9%) of the subjects had symptoms when infected with COVID-19. There was a significant relationship between the level of 25(OH)D3 (p=0.001) and the status of the COVID-19 vaccine (p=0.013) with the presence of symptoms in COVID-19 patients.Conclusion: The lower the level of 25(OH)D3 in the blood and the more incomplete the COVID-19 vaccine, the greater the onset potential of COVID-19 symptoms. It is necessary to maintain vitamin D intake and increase the coverage of the COVID-19 vaccine, especially at booster doses.Keywords: vitamin D, COVID-19, vaccination, health protocol